Ici et Là-bas : entre territorialités de l’entre-deux et morcellements identitaires - Dominique Chevalier (Espace populations sociétés, 2009)
This paper seeks to understand how a group of youngsters of South-Moroccan background try to reconcile the need to be from « here », i.e. urban, poor and sometimes discriminated against and at the same time to be from « over there », i.e. a rural place where they make their peers and neighbours jealous and where they are considered affluent in a land of scarcity. This perpetual « switch of identity » as Y. Charbit, M.-A. Hily and M. Poinard put it, is analysed through their spatial practices, in France and in Morocco, through the time they spend in the country their parents came from, through the way they perceive social interactions and travels abroad as well as through the way they define the places they live in.